Gaya Komunikasi Kepemimpinan Rektor Universitas Negeri Padang: Studi Kasus pada Prof. Ir. Ganefri, P.hD. Periode 2016-2024 - Hamdi, Furqanul; Roem, Elva Ronaning; Arif, Ernita (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Leadership communication in public universities is a complex process, as rectors must translate institutional vision into messages that can be understood by academic staff, administrative personnel, and governance bodies. This study analyzes the leadership communication style of Ganefri as Rector of Universitas Negeri Padang during the 2016–2024 period, focusing on the dominant communication style and its expression in formal and informal contexts. This research uses a qualitative case study approach involving six key informants. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that Ganefri’s leadership communication style is predominantly structured, regulation-based, evidence-oriented, and clarity-centered. In formal settings, his communication is precise, participatory, and oriented toward accountable collective decision-making. In informal contexts, his communication becomes more fluid, personal, and relational, while still conveying strategic messages. This study concludes that effective leadership communication in higher education requires a balance between regulatory firmness and relational warmth.